Qualia bona in coniuge sunt quaerenda.... Zalecenia na temat wyboru żony w świetle średniowiecznych traktatów o wychowaniu (na przykładzie De regimine principum Idziego Rzymianina) - Brzeziński, Witold (Biuletyn Historii Wychowania, 2014)
The paper is concerned with the advice regarding choosing a wife presented in the thir-teenthcentury educational treatise De regimine principum by Giles of Rome. It was the most popular “mirror of prince” in the later Middle Ages. In defining the criteria one should pay attention to Giles distinguishes three kinds of “goods” (bona) that an appro-priate wife-to-be should possess. These are the so-called external (exterior) goods and internal (interior) ones, the latter being in turn divided into the bodily goods (bona cor-poris) and the spiritual goods (bona animae). The first kind includes such goods as noble descent (nobilitas generis), multitude of friends (pluralitas amicorum) and abundance of wealth (multitudo divitiarum); the second – beauty (pulchritudo) and size (magnitudo); the third – self control (temperantia) and liking for work (amor operositatis). These three kinds of goods, as well as particular examples of them, are drawn by Giles from Aristotle’s Rhetorica. Yet, when compared to those enumerated by medieval theologians and canon lawyers in their discussons of reasons for marrying, they do not considerably differ from them. What matters is that Giles sees and accepts all of them as relatively equally important as criteria used for choosing a wife. This is because they are all neces-sary for setting up a successful marriage that will bring happiness to a man.